Kritik Sosial dalam Lirik Lagu “Indonesia” Karya Rhoma Irama - Moh Muzakka (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
Rhoma Irama is a multi-talented artist who is very popular today. He has created many songs with many themes as well. One of the songs that voiced about nationalism, titled